Effectiveness Of Reward And Punishment On Student Learning Discipline - Siti Nuraisah; Risda Yeni; Miftahir Rizqa (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Discipline is one of the ways to correct deviant or incorrect behavior. Additionally, discipline also provides motivation,guidance, and support to students to achieve satisfaction through obedience. One strategy that teachers can implement to improve students discipline is through the use of rewards and punisment. Rewards are a form of positive reinforcement that shows appreciation to students. On the other hand, punishments are a type of negative reinforcement, however, when applied correctly and reasonably, they can serve as a tool to discipline students. This study aims to assess the effectiveness of providing rewards and punishment in improving students discipline levels. The approach used in this research is the literature review method. The findings from the research indicate that the implementation of rewards and punishments is highly effective in fostering students disciplinary attitudes in the learning process. The provision of rewards an punishments can help students become more active in the learning process and adhere to the school regulations